2021
DOI: 10.1177/19485506211039101
|View full text |Cite
|
Sign up to set email alerts
|

Perceiver Effects in Person Perception Reflect Acquiescence, Positivity, and Trait-Specific Content: Evidence From a Large-Scale Replication Study

Abstract: Person judgments reflect perceiver effects: differences in how perceivers judge the average person. The factorial structure of such effects is still discussed. We present a large-scale, preregistered replication study using over 1 million person judgments (different groups of 200 perceivers judged 200 targets in one of 20 situations, using 30 personality items). Results unanimously favored a model comprising three systematic components: acquiescence (endorsing all items more than other perceivers), positivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…As a consequence, the general factor labelled "positivity" also tapped acquiescence variance, that is, differential tendencies to prefer positive or negative response options irrespective of an item's content. Whereas prior research has shown that positivity differences contribute more to perceiver effects than do acquiescence differences (Heynicke et al, 2021;Rau, Carlson, et al, 2021), we were not able to separately test the influence of either tendency when computing assumed similarity correlations.…”
Section: Studymentioning
confidence: 65%
See 2 more Smart Citations
“…As a consequence, the general factor labelled "positivity" also tapped acquiescence variance, that is, differential tendencies to prefer positive or negative response options irrespective of an item's content. Whereas prior research has shown that positivity differences contribute more to perceiver effects than do acquiescence differences (Heynicke et al, 2021;Rau, Carlson, et al, 2021), we were not able to separately test the influence of either tendency when computing assumed similarity correlations.…”
Section: Studymentioning
confidence: 65%
“…None of the present authors were involved in data collection. Parts of the data used here have already been included in other publications on interpersonal perception (Heynicke et al, 2021;Wiedenroth, Unkelbach, et al, 2021;Wiedenroth & Leising, 2020). Crucially, none of these previous papers and analyses used the perceivers' self-reports.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may reflect stable, trait-level idiosyncrasies such as personality, stereotype knowledge, response style, or state-like influences such as affective state, evaluative context, external environment, or psychological situations. Recent work suggests that perceivers' stereotype knowledge and lay theories of personality play a role (Stolier et al, 2018(Stolier et al, , 2020Xie et al, 2021), as well as their degree of acquiescence and positivity bias (Heynicke et al, 2021). However, these factors do not explain all perceiver variance, and other sources of perceiver-level variance are likely important.…”
Section: Variability In Facial First Impressionsmentioning
confidence: 99%
“…Estimates of the total influence of different types of perceiver variance on personality judgments often range around 30% (Kenny, 2020;Rau et al, 2021). However, when studies do not permit interaction between perceivers and targets, estimates can be considerably lower (e.g., Heynicke et al, 2021). One reason for this could be that, in studies with previous interactions, the variation between perceivers' judgment styles may be increased by variation in the average target's behavior toward particular perceivers (e.g., one perceiver actually being treated more nicely by everyone than another perceiver).…”
Section: Core Findings Using the Variable-centered Approachmentioning
confidence: 99%